NILAI-NILAI MODERASI BERAGAMA DALAM PENDEKATAN DAKWAH - Sirajudin; Fitriani, Lina Ulfa (STIT Al-Aziziyah, 2024)
Mainstreaming religious moderation is considered very urgent recently, due to the existence of extreme or deviant understandings of religion. So that, it requires a straight and moderate thought or understanding and mindset, and not excessively implementing Islamic values ​​in social, national and state life. Of course, what is undesirable to happen is the emergence of acts of violence or radicalism and destruction in the name of religion. With the triggers above, narrow thinking that is not moderate gives rise to ideas, the idea of ​​creating a government program on mainstreaming religious moderation, as a concrete effort toward off erroneous understandings that tend to be extreme. Religious teachings always carry a mission of peace, harmony, unity and harmonization of diversity as well as upholding the values ​​of justice and guaranteeing the human rights of every citizen. One of the efforts that needs to be made at this time is to convey the values ​​of religious moderation or wasathiyyah through tabligh pulpits, Islamic da'wah, especially since the challenges of da'wah in the contemporary era are very complex, so a soothing, moderate way of preaching is needed in conveying religious messages to people to intertwine ukhuwah Islamiyah, Ukhwuah Wathoniyah and Ukhwuah Basyariyah. Da'wah is part of the process of activity and persuasion which is leads to convey the messages of Islamic teachings, change and development and exemplary work organized into a da'wah system.